VO2max and the kinetics of VO2, muscle oxygen delivery, and muscle deoxygenation - Marinari, G.; DeLorey, D. S. (Frontiers in Physiology, 2025)
Introduction: Aerobic fitness and oxygen uptake kinetics (tVO2) at the onset of exercise appear to be inversely correlated, however, the mechanisms underlying changes in tVO2 across different levels of aerobic fitness have not been elucidated. The purpose of this study was to investigate the relationship between maximal VO2 (VO2max) and tVO2 and determine whether the capacity to deliver or to utilize O2 limits tVO2 in an aerobic fitness dependent manner.